VP87 Extrapolation From Progression Free Survival To Overall Survival In Oncology. (12th January 2018) - Fischer, Alastair; Latimer, Nicholas; Henshall, Chris; Hernandez-Villafuerte, Karla
Abstract : INTRODUCTION: The outcomes from clinical and other healthcare trials of most interest to patients and health systems are usually increases in the quality and length of life (overall survival (OS)). This poses a problem, because complete knowledge on the true increase in OS is not available until the last person in the trial dies. However, if OS is sufficiently correlated with a surrogate endpoint that is observable within the trial period or soon after the treatment has finished, this can be used to estimate OS, without much error. The most widely-used surrogate endpoint in oncology is progression-free survival (PFS). We aim at (i) analyzing the methods used to extrapolate from PFS to OS in the field of oncology; (ii) identifying whether a clear guidance exists in the literature about what is considered to be 'best practice' in extrapolation from PFS to OS; (iii) determining the key limitations, weaknesses and gaps in the current literature and method used to test PFS surrogacy. METHODS: We extend the literature review carried out previously (1), we interview experts from regulatory and reimbursement bodies, and we explore academic research into the methodology of surrogacy and the need for better reporting of surrogacy papers. RESULTS: A number of factors affect the relationship between PFS and OS. Therefore, there is no unique correct answer for the question of whether PFS is an appropriate surrogate for OS in oncology. Many of these factors are related to the length and characteristics of post-progression survival (PPS). CONCLUSIONS: Any consideration of evidence relating to PFS should consider both tumour type and other factors, particularly those related to PPS. Protocols of future follow-up of clinical trial patients should specify procedures for gathering information about the effect of post-progression management of the disease. This should allow stronger conclusions to be extracted from statistical analyses. Improved reporting standards will aid in achieving this goal. In addition, it is very likely that increasing the use of IPD will result in greater precision in estimating the benefits of worthwhile drugs.